2017
DOI: 10.3126/ojn.v7i1.18893
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Malocclusion in Orthodontic Patients in South-Eastern Region of Nepal

Abstract: Introduction: Occlusal traits in orthodontic patients have been studied in different parts of Nepal. However, very few data are available on malocclusion in south-eastern region of Nepal.Objective: To assess the pattern of malocclusion occurring in orthodontic patients in south-eastern region of Nepal, and to estimate the age of presentation of Class II malocclusion among the patients. Materials & Method:Data were collected from 150 pre-treatment study models and lateral cephalograms from two orthodontic speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
1
1
1
Order By: Relevance
“…9 The results of the present study showed that females were more interested toward orthodontic treatment with the frequency of 70%. This study is in accordance with the study done by Acharya et al 10 and also nearly similar to study done by Rahman et al 9 It was suggested the causes would be for marriage reason or self-consciousness.…”
Section: Discussionsupporting
confidence: 93%
“…9 The results of the present study showed that females were more interested toward orthodontic treatment with the frequency of 70%. This study is in accordance with the study done by Acharya et al 10 and also nearly similar to study done by Rahman et al 9 It was suggested the causes would be for marriage reason or self-consciousness.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for undergoing Orthodontic treatment for matrimonial reasons was answered positively by majority of the participants mostly female subjects and this was the most popular reason for seeking Orthodontic treatment which is in alignment with the study by Rahman et al [18] and Acharya [19] who stated marriage as the major cause for seeking Orthodontic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted in the western terai region of Nepal found that the positive cases of piroplasm in cattle were between 10% and 19.3% [ 18 , 19 , 20 ]. Other studies conducted in different regions of Nepal found that the positive cases of piroplasm in cattle were higher than the present study: 72.2% (121/163) in the eastern part of Nepal (clinical diagnosis), between 50% and 75% [ 18 , 19 , 21 , 22 , 23 , 24 ]. In India, the prevalence of piroplasm ranges from 2% to 33%, depending on the region [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 76%